2013
DOI: 10.1177/1744629513503590
|View full text |Cite
|
Sign up to set email alerts
|

Using goal analysis to drive improvements in performance and outcomes

Abstract: Economic pressures for public health and human services systems to control budgets are increasing the need for demonstrating value of support services provided to persons with intellectual disabilities. In this article, we build from earlier work that presented a method for assessing goal attainment to expand the study of goal characteristics as a means to gain an improved understanding of individual outcomes and service performance. The study results suggest a positive relationship between targeting intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A second implication of the present study is the need to focus on the whole person as reflected in the eight QOL domains used as framework of the content analysis. Most of the goals analysed in the present study related to the domain of physical well‐being, as was also found by Lawlor et al (). This can be explained by the fact that people with ID are more at risk for health problems than the general population, and that these risks increase with age, severity of the ID and specific syndromes (Schoufour et al ; Havercamp & Scott ; Hermans & Evenhuis ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second implication of the present study is the need to focus on the whole person as reflected in the eight QOL domains used as framework of the content analysis. Most of the goals analysed in the present study related to the domain of physical well‐being, as was also found by Lawlor et al (). This can be explained by the fact that people with ID are more at risk for health problems than the general population, and that these risks increase with age, severity of the ID and specific syndromes (Schoufour et al ; Havercamp & Scott ; Hermans & Evenhuis ).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of both natural and service‐based resources in achieving ISP goals was found in 25.9% of all goals. These findings are in line with policy developments promoting the involvement of natural resources and the persons' individual role and responsibility in working to QOL‐related outcomes (Kober & Eggleton, ; Lawlor et al , ). The findings of the present study are congruent with a shift being made from a predominant specialised services approach in which these services are ‘used to the maximum extent’ to an approach in which different resources are blended into an individualised strategy of supports (Luckasson et al , , p.184).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation